2016
DOI: 10.4070/kcj.2016.46.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Plaque Composition in Coronary Chronic Total Occlusion Lesion Using Virtual Histology-Intravascular Ultrasound

Abstract: Background and ObjectivesSuccess rates of chronic total occlusion (CTO) percutaneous coronary intervention (PCI) have recently been reported to range from 80% to 90%. A better understanding of the pathologic characteristics of the CTO lesion may helpful to improving CTO PCI success rates. We evaluated the CTO lesion in patients with stable angina (SA) by virtual histology-intravascular ultrasound (VH-IVUS).Subjects and MethodsThe study population consisted of 149 consecutive patients with SA underwent VH-IVUS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The analysis and comparison of the nonculprit plaques of two distinct diagnoses, that is, STEMI and CTO, may provide a better understanding of the plaques. Especially nonculprit proximal plaques of CTO lesions showed a similar plaque composition to the CTO lesion 5, which was a distinct characteristic compared with that of stable nonocclusive coronary diseases 6.…”
Section: Introductionmentioning
confidence: 82%
“…The analysis and comparison of the nonculprit plaques of two distinct diagnoses, that is, STEMI and CTO, may provide a better understanding of the plaques. Especially nonculprit proximal plaques of CTO lesions showed a similar plaque composition to the CTO lesion 5, which was a distinct characteristic compared with that of stable nonocclusive coronary diseases 6.…”
Section: Introductionmentioning
confidence: 82%
“…Except for proximal and distal fibrous caps, the occluded segment materials were biologically active with inflammation, neovascularization, and recanalization, giving rise to different CTO compositions. Similar to non-CTO lesions in patients with stable angina, the composition of CTO lesions mainly consists of three types, namely, necrotic core, fibrous, and dense calcium ( 17 ). Previous studies exploring GW crossing predictors always focus on the severity of calcification in terms of plaque characteristics, which revealed that calcification is likely to be a predictive factor of failed GW crossing within 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…The body frequently contains some degree of neovascularization, dense fibrous tissue, atheroma, calcified tissue, and focal lymphocyte infiltrate [31]. This type of lesions could involve a long coronary segment with a large plaque burden [32]. A study conducted by Guo et al using intravascular ultrasounds virtual histology (IVUS-VH) to evaluate CTO lesion characteristics, revealed the presence of two relatively different CTO plaque types: one presenting a large amount of necrotic core, possibly deriving from ruptured plaques associated with previous acute coronary syndromes, and the other one characterized by a little or absent necrotic core, compatible with slowly evolving plaques.…”
Section: Morphological Characteristics Of Ctomentioning
confidence: 99%